LAYANAN VIDEO SHARING SOSIAL SEBAGAI PANDUAN PEMANFAATAN LIMBAH NON ORGANIK DAN ORGANIK DI DINAS KEBERSIHAN KOTA KUPANG BERBASIS WEB RESPONSIVE - Detaq, Civrandy Okri Purnandy; Lenggu, Max Abr Soleman; Payong, Yohanes (HOAQ (High Education of Organization Archive Quality) : Jurnal Teknologi Informasi, 2020)
Waste is a waste product produced by both industrial and domestic production (household), its presence at a certain time and place is undesirable because it has no economic value. Chemically verified, this waste includes organic chemicals (waste that can be decomposed: leaf residue, food particles) and non-norganic (waste that cannot be decomposed: metal, plastic). At certain concentrations and levels, the presence of waste may have a negative impact on the environment, in particular on human health. Therefore, it is necessary to handle the waste. Measures must be taken to reduce the amount of waste generated by use. Video sharing services based on this site is a support solution for the Department of Sanitation of the city of Kupang in dealing with the problems of waste that occur in the community, in particular directly raising awareness of the community to each other to motivate others in the use of waste generated.